Penggunaan Media Sosial Dalam Penguatan Literasi Siswa Pada Pembelajaran PAI Di SMA Negeri 1 Kencong - Nisa’, Fikri Khoirun; Jannah, Nur (Al-Ulum: Jurnal Pendidikan Islam, 2024)
With the increasing sophistication of technology, the use of social media by students has a significant impact on their literacy skills. Reportal data proves that the number of social media users in Indonesia reached 191.4 million in January 2022, this is equivalent to 68.9% of the total population in Indonesia. This research uses qualitative methods with descriptive research types. The subjects of the study consisted of several students, PAI teachers, and other educators. Using this method, this study aims to explore various initiatives for the practice of using social media as a reinforcement of student literacy in PAI teaching. The results showed that the use of social media in PAI learning can affect the intensity of students' literacy skills. Providing educational content, facilitating understanding, encouraging independent learning, stimulating creativity, and improving digital literacy are some of the benefits of using social media in PAI learning. In addition, online discussion sessions as well as collaborative projects can enhance students' understanding of PAI material and improve their literacy skills. The use of social media in PAI learning can help students improve their literacy, criticism, and creativity skills in learning.